The role of economic, social & poilitical integration of World Trade Organisation - Islam, Rabiul; Omar, Rusdi; Khamis, Kamarul Azman; Yatiban, Aminurraasyid (IAEME Publication, 2020)
The factors of this paper discover the roles of economic, social & political integration of world trade organisation in the era of developing world. The expositions of problems that may impact the trade among developing countries form the conceptual basis for the design of the research instrument used for this study. Data for this study were obtained from vigorous literatures on economic, social & political integration of world trade organisation as well. The style greatly relied on energetic prior literatures on the subject organism arrangement with. The findings indicate that the co-existence of the trade among developing countries and the now technical industrial sectors, where the service economy and the hard-goods manufacture have little or no connection with the natural features and climatology of the earth, and there is no mixed-mode which analogizes the realism of the initial planet. Further continuation of the genuine likelihood of unrelenting mass regular disasters in this land, and the truth of the inhabitant’s concentration and cruelty of the authority of the land to provide for its own populace, cannot be gathered into any known operate between nation to nation.